Potency evaluation of different GNRH analogues on ovulation induction and reproductive performance of doe rabbit - Viudes-De-Castro, María P.; Marco-Jiménez, Francisco; Miralles-Bover, H.; Vicente, José S. (Wiley, 2024)
Gonadotropin-releasing hormone (GnRH) -supplemented extenders have emerged as a welfare-orientated method to induce ovulation in the artificial insemination (AI) of rabbits. The main factor that limits the bioavailability of GnRH analogue on intravaginal administration is the proteolytic activity of enzymes present in rabbit seminal plasma. The use of GnRH analogues with higher biological potency would allow us to decrease their concentration in the seminal dose without compromising effectiveness. The current study was designed to assess the efficacy of various GnRH analogues concerning their ability to induce ovulation in rabbit AI. The base solution used for experimental extenders contained an aminopeptidase inhibitor. Four experimental groups were used, females from the Control group were induced to ovulate with an intramuscular administration of 1 μg of buserelin, while in the other three groups females received an intravaginal administration of 3.5 μg of buserelin (BUS), deslorelin (DES) or fertirelin (FER) within the seminal dose. Results showed that the ovulation frequency was similar in all groups studied. A concentration of 3.5 μg of the different GnRH analogues tested in this study showed similar potency in inducing ovulation in non-lactating females, yielding comparable results in terms of pregnancy rate at birth and prolificacy.